1985
DOI: 10.1180/claymin.1985.020.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-bearing clay minerals: I. Optical spectroscopic study of nickel crystal chemistry

Abstract: A B S T R A C T:Nickel crystal chemistry was systematically studied in various phyllosilicates, mainly the natural phases selected from the 'garnierites' of the supergene ore deposits of New Caledonia. Minerals which do not usually occur in New Caledonian parageneses were synthe sised, as they could represent intermediate phases of genetic importance. In the kerolitepimelite series, a linear relationship occurred between the ratio I (13,20~/I(02,11 ) of the hk bands and Ni-content. Diffuse reflectance spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
6
34
0
Order By: Relevance
“…20 The spectrum of the untreated Ni/CeO 2 sample can be analyzed as the superposition of the spectra of Ni(OH) 2 and The band observed at 1120 nm for Ni(OH) 2 is shifted to 1230 nm for Ni/CeO 2 , probably because of a crystallinity effect, Ni II ions in a poorly organized deposit being submitted to a weaker crystal field than in crystalline Ni(OH) 2 . 23 Furthermore, two very broad bands indicate a distribution of hexacoordinated Ni II species. According to Tanabe-Sugano diagrams, 26 their average positions (λ 2 , λ sf ) 820 nm and λ 1 ) 1400 nm), indicate that the Ni II ions involved are submitted to very weak crystal fields.…”
Section: Resultsmentioning
confidence: 99%
“…20 The spectrum of the untreated Ni/CeO 2 sample can be analyzed as the superposition of the spectra of Ni(OH) 2 and The band observed at 1120 nm for Ni(OH) 2 is shifted to 1230 nm for Ni/CeO 2 , probably because of a crystallinity effect, Ni II ions in a poorly organized deposit being submitted to a weaker crystal field than in crystalline Ni(OH) 2 . 23 Furthermore, two very broad bands indicate a distribution of hexacoordinated Ni II species. According to Tanabe-Sugano diagrams, 26 their average positions (λ 2 , λ sf ) 820 nm and λ 1 ) 1400 nm), indicate that the Ni II ions involved are submitted to very weak crystal fields.…”
Section: Resultsmentioning
confidence: 99%
“…The shoulders at 22,400 and 27,300 cm x are in the same energy region as in nontronite (Bonnin et al, 1985) and are due to octahedral Fe 3+ atoms. The two other absorption bands at lower energy are due to Ni in 6-fold coordination (Manceau et al, 1985). These latter authors showed that the energy of the crystal field band at 9000 cm -~ depends on the type of Ni-bearing phyl-J I I 12000 9,000 6,000 WAVENUMBER (cm-1) Figure 6.…”
Section: Diffuse Reflectance Spectroscopic Resultsmentioning
confidence: 99%
“…In diffuse reflectance spectra of Ni-bearing phyllosilicates, for instance, such splitting is attributed to the low symmetry of the coordination octahedron of Ni 2+ (e.g. Manceau et al 1985, Manceau andCalas 1987). However, in the type I spectra of our pyroxenes this band is seen as a singular band slightly overlapped by the much weaker spin-forbidden band c. This observation is supported by results of the curve resolution of the Ni 0.3 pyroxene spectrum showing that all three spin-allowed bands a, b and e, as well as the two spin-forbidden ones, c and d, can be satisfactory approximated by singular Gaussians (Fig.…”
Section: Resultsmentioning
confidence: 99%